Conflicts in the Middle East since 1945 - Milton-Edwards, Beverley; Hinchcliffe, Peter (New York : Routledge, 2008)
"This third edition of Conflicts in the Middle East since 1945 analyses the nature of conflict in the Middle East, with its racial, ethnic, political, cultural, religious and economic factors. Throughout the book Peter Hinchcliffe and Beverley Milton Edwards put the main conflicts into their wider context, with thematic debates on issues such as the emergence of radical Islam, the resolution of conflicts, diplomacy and peacemaking, and the role of the superpowers." "The book is brought fully up to date with events in the Middle East, covering, for instance, developments in 2006 in Iraq, where a democratically elected government is in place but the insurgency shows no sign of coming under control. The analysis of the Palestinian-Israeli conflict is also brought up to the present day, to include the election of the Hamas government and the 2006 conflict between Israel and Lebanon's Hizballah." "Including a newly updated bibliography and maps of the area, this is the perfect introductionfor all students wishing to understand the complex situation in the Middle East, in its historical context."--BOOK JACKET.
1. The Arab-Israeli conflict: ways of war -- 2. The Palestinian-Israeli conflict: hostages to history -- 3. Superpower conflict in the Middle East: war by proxy -- 4. Generation jihad: conflict in the name of Islam? -- 5. Sectarian conflict: Lebanon, state without a nation -- 6. Ethnic conflict: the forgotten Kurds -- 7. War in the Gulf: Iran and Iraq, 1980-1989 -- 8. The Kuwait crisis: brother versus brother -- 9. The politics of conflict and failure of peacemaking -- 10. No end to the storm: 9/11 and the war in Iraq.
Includes bibliographical references and index.
Keywords: Mediation, International; Middle East -- Politics and government -- 1945-